2019
DOI: 10.11648/j.ijae.20190402.15
|View full text |Cite
|
Sign up to set email alerts
|

Constraints of Agricultural Input Supply and Its Impact on Small Scale Farming: The Case of Ambo District, West Shewa, Ethiopia

Abstract: Agriculture is a principal economic activity mainly for those developing countries. This study was intended to analyze the impact of agricultural input supply on small scale farming in the study area; to examine the trends and forms of farming practiced by the farmers, to identify the farm input constraint existed in the study area, to assess input supply and its link with forms of farming. Both primary data and secondary were used for the study. In the survey three different forms of farming were identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Farmers are unwilling to adopt row planting with local varieties in the study area. This nding is consistent with the study [10,39]. However, this result contradicts the nding [69], which found that farmers with small and marginal plots are more likely to adopt than farmers with large plots.…”
Section: Adoption Status Of Maize Technology Packagessupporting
confidence: 89%
See 1 more Smart Citation
“…Farmers are unwilling to adopt row planting with local varieties in the study area. This nding is consistent with the study [10,39]. However, this result contradicts the nding [69], which found that farmers with small and marginal plots are more likely to adopt than farmers with large plots.…”
Section: Adoption Status Of Maize Technology Packagessupporting
confidence: 89%
“…Even though Ethiopia has a rich agricultural history, it has been facing many challenges in the sector. Agricultural productivity is low due to a lack of private investment, fragmented markets, farmers' limited access to resources, low subsidies, soil degradation, low application of modern agricultural inputs, ine ciencies, subsistence farming, poor infrastructure, vulnerability to environmental and climate-related shocks, reliance on outdated farming methods, and rain-fed agriculture leading to uctuations in yields [6][7][8][9][10][11]. Non-stop internal con ict and the worst drought in recorded history are a factor in the worsening of these challenges.…”
Section: Introductionmentioning
confidence: 99%
“…They are inefficient compared to the demand of the farmers on the ground. The price of inorganic fertilizer by itself is unaffordable for the poor farmers which highly influence the farmers' decision to, or not to use inorganic fertilizer (KENEA et al, 2019). Setit Humera district among the potential area of sesame farming in Ethiopia has been facing many farming problems, such as yearly variability of rainfall, reduced soil fertility, and market fluctuation mainly for Sesame.…”
Section: Introductionmentioning
confidence: 99%
“…The educational status of the farmers was an important factor affecting usage of agricultural inputs. The higher the educational level of the farmer the better is their understanding of improved agricultural technologies (Kenea et al, 2019).…”
Section: Socio-economic Characteristics Of Respondentsmentioning
confidence: 99%
“…The result supports the findings of Olagunju and Ogunniyi (2006) that most of the farmers in Southwestern Nigeria cultivated small areas of land. Land size is an important factor affecting the demand for agricultural inputs because the increase in size of land holdings encourages more crop production and invariably provides sufficient income and there by funds to purchase modern farm inputs (Kenea et al, 2019). About 55.0% of the respondents acquired land through inheritance, while 2.5% and 0.8% purchased and rented their lands, respectively.…”
Section: Socio-economic Characteristics Of Respondentsmentioning
confidence: 99%